Activity Integration Coding Kids for Early Childhood Literacy Development - Erlin Haniah; Junita Dwi Wardhani (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to integrate Coding Kids activities for the development of early childhood literacy. Methodology: The research method uses a qualitative approach with a case study design. Data collection methods in this study include observation, interviews, and documentation. Observations were conducted at BA Aisyiyah V Karangjati, Sragen, specifically for group B with 14 students. The data validity used in this study is source triangulation and technical triangulation. The data analysis technique is carried out by data reduction to group data obtained from observations, interviews, and documentation. Data presentation is used to present grouped data in the form of descriptive narratives, tables, or diagrams that facilitate understanding. Conclusions are drawn to summarize the results of all the data that has been collected, by ensuring that the conclusions answer the research questions that have been formulated. Results: The results of the study showed that the Coding Kids activity based on Unplugged Coding in developing early literacy in early childhood showed good and positive results, so that children were able to experience improvements in recognizing, understanding words, spelling, reading and being able to write by deciphering letters to form words. Applications/Originality/Value: The findings of this study can be used as a reference for early childhood teachers in developing early literacy in reading and writing with Coding Kids media based on Unplugged Coding.